Green Sukuk for Sustainable Development Goals A Maqāṣid Perspective: Systematic Review and Meta-Analysis - Khusna Khanifa, Nurma; Khoiri, Ahmad; Mulyani, Rita (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
The environmental crisis is characterized by climate change with an increase in the earth's average temperature of 1.50 - 2.00 Celsius. Climate change can increase the risk of hydrometeorological disasters by 80% of the total disasters that occur in Indonesia. Overcoming the impacts of climate change requires a lot of money. One form of funding instrument to overcome the impact of climate change is green sukuk. Research Objective to critically analyze the trend of green sukuk research in Indonesia. This type of research is a literature review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) through four (4) stages, namely identification, screening, eligibility and included. The results showed that the green sukuk trend has dominated in the development of SDGs over the past 3 years. The issuance of green sukuk has contributed to the achievement of the Sustainable Development Goals (SDGs) Framework. From the maqāṣid al-sharī`ah framework through the interrelated hierarchy of the system of Islamic law approach, green sukuk used for eligible green projects fall into the urgency of al-ḍarūrīyah, al-ḥājīyah and al-taḥsīnīyah. The benefit created is maqāṣid al-khāṣṣah which is in line with QS. From these two (2) verses, there is a basic objective of sharia, namely hifẓ al-bi`ah. It is necessary to expand uṣūl al-khamsah by adding one component of hifẓ al-bi`ah (becoming uṣūl al-sittah). So that maqāṣid al-sharī`ah can accommodate universal benefits in response to increasingly severe environmental damage. Green sukuk has the scope of hifẓ al-bi`ah within the framework of maqāṣid al-sharī`ah including mitigation (al-ḍarūrīyah), adaptation (al-ḍarūrīyah), environment (SDGs) (al-ḥājīyah), social - economic (SDGs) (al-taḥsīnīyah), and governance (al-taḥsīnīyah).